Inflammatory bowel disease in pregnancy: a population‐based study of prevalence and pregnancy outcomes. (29th February 2016) - Shand, AW; Chen, JS; Selby, W; Solomon, M; Roberts, CL
Abstract : Objective: To determine the prevalence of the inflammatory bowel diseases (IBD), ulcerative colitis (UC) and Crohn's disease (CD), in pregnant women and determine pregnancy and fetal/neonatal outcomes. Design: Population‐based cohort study. Setting: New South Wales, Australia, 2001–11. Population: A total of 630 742 women who delivered at ≥20 weeks of gestation. Methods: Descriptive and multivariate regression analyses of perinatal data linked to hospital admission data. We compared birth outcomes of women with and without a documented diagnosis of IBD. Main outcome measures: Caesarean section, severe maternal morbidity, preterm birth <37 weeks of gestation, planned preterm birth, small‐for‐gestational‐age (birthweight <10th centile), perinatal mortality (stillbirth/neonatal death ≤28 days). Results: In all, 1960 women (0.31%) with IBD, who had 2781 births (1183 UC, 1287 CD and 311 IBD‐indeterminate). Women with IBD were more likely than women without IBD to have a caesarean section [41.5 versus 28.2%, adjusted risk ratio (aRR) 1.38, 95% CI 1.31–1.45], severe maternal morbidity (2.6 versus 1.6%, aRR 1.54, 95% CI 1.17–2.03), preterm birth (9.7 versus 6.6%, aRR 1.47, 95% CI 1.30–1.66), planned preterm birth (5.3 versus 2.9%, aRR 1.74, 95% CI 1.47–2.07), and their infants to be small‐for‐gestational‐age (9.7 versus 9.5%, aRR 1.19, 95% CI 1.04–1.36). There was no evidence of a difference in perinatal mortality. Conclusion: Pregnancy‐associated IBD is more common than previously reported. Pregnancies complicated by IBD at or near the time of birth have significantly higher rates of adverse pregnancy outcomes than pregnancies of women without IBD. Tweetable abstract: Increased rates preterm birth and caesarean section in women with inflammatory bowel disease. Tweetable abstract: Increased rates preterm birth and caesarean section in women with inflammatory bowel disease.